Kekuatan Dimensi Kualitas Pelayanan dalam Menjaga Loyalitas Nasabah pada Jasa Asuransi - Dara Balinda Utami Nur Islam; Erry Sunarya; Asep M Ramdan (IPM2KPE, 2022)
This study aims to determine the effect of the strength of service quality dimensions on customer loyalty at the Sukabumi Life Vision Agency Insurance Service (PT. Prudential Life Assurance), and to see how much influence the strength of service quality has on customer loyalty either partially or simultaneously. This research method is an associative descriptive method with path analysis as a data analysis technique. The results showed that the quality of service through the dimensions of Tangible, Reliability, Responsiveness, Assurance, and Empathy on customer loyalty had a simultaneous effect on customer loyalty at the Life Vision Agency Sukabumi Insurance Service (PT. Prudential Life Assurance), this was indicated by the total direct and indirect effect. indirect amounted to 6.601293138%. Service quality through the dimensions of Tangible, Reliability, Responsiveness, Assurance, and Empathy has a partial effect on customer loyalty at the Sukabumi Life Vision Agency Insurance Service (PT. Prudential Life Assurance) namely Tangible by 5.060%, Reliability by 8.684%, Responsiveness by 11.317%, Assurance of 11.927% and Empathy of 8.596% of the five dimensions show that the most dominant influence on Customer Loyalty at Life Vision Agency Sukabumi are Reliability/ Reliability, Responsiveness/ Responsiveness, and Assurance/ Guarantee. In conclusion, the more reliable the Agent and responsive in providing services and security in the transaction and administrative processes, the more Customer Loyalty to Life Vision Agency Sukabumi will increase. Keywords: Service Quality, Customer Loyalty